Carbamazepine Enhances Adipogenesis by Inhibiting Wnt/β-Catenin Expression - Dong Uk Im; Sang Chon Kim; Gia Cac Chau; Sung Hee Um (Cells, 2019)
Carbamazepine is a drug that is widely used in the treatment of epilepsy and bipolar disorder. The prevalence of obesity in patients treated with carbamazepine has been frequently reported. However, whether carbamazepine affects adipogenesis, one of the critical steps in the development of obesity, remains unclear. Here, we show that carbamazepine increased the expression levels of peroxisome proliferator-activated receptor γ (PPARγ), CCAAT/enhancer-binding protein β (C/EBPβ), and fatty acid synthase (FASN) in 3T3-L1 cells. Notably, carbamazepine inhibited the expression levels of β-catenin, a negative regulator of adipogenesis, leading to enhanced adipogenesis. Conversely, β-catenin overexpression abolished the effect of carbamazepine on adipogenic gene expression. However, depletion of β-catenin further enhanced PPARγ expression. In addition, carbamazepine reduced β-catenin expression by lowering the levels of phospho-low density lipoprotein receptor-related protein 6 (p-LRP6) and phospho-glycogen synthase kinase 3β (p-GSK3β) in Wnt/β-catenin signaling. Moreover, carbamazepine reduced Wnt mRNA expression and decreased the promoter activities of TCF, the target of β-catenin during adipogenesis. These results suggest that carbamazepine enhances adipogenesis by suppressing Wnt/β-catenin expression, indicating its potential effects on obesity-related metabolism.